The Impact of Strategic Leadership Styles and Knowledge Sharing on Employee Performance (Case Study: Employees of Imam Khomeini Airport) - Boghosian, Albert; Azmi, Kimia (Management Strategies and Engineering Sciences, 2026)
In this regard, the aim of the present study was to investigate the impact of strategic leadership styles and knowledge sharing on employee performance at Imam Khomeini Customs. This study was applied in terms of purpose and descriptive-survey in terms of data collection method. The statistical population of this study consisted of all managers and employees of Imam Khomeini Customs, from whom 197 individuals were selected using Cochran’s formula and convenience sampling. A researcher-developed questionnaire was used to collect the required data. Its validity was finalized after applying the supervisor’s comments, and its reliability was confirmed using Cronbach’s alpha coefficient (greater than 0.70). The findings were analyzed using structural equation modeling and Smart PLS software. The research findings indicated that transformational leadership style affects employee performance at Imam Khomeini Customs. Transactional leadership style affects employee performance at Imam Khomeini Customs. Charismatic leadership style affects employee performance at Imam Khomeini Customs. Transformational leadership style affects knowledge sharing at Imam Khomeini Customs. Transactional leadership style affects knowledge sharing at Imam Khomeini Customs. Charismatic leadership style affects knowledge sharing at Imam Khomeini Customs. Knowledge sharing affects employee performance at Imam Khomeini Customs. The results showed that transformational leadership style (β = 0.271), transactional leadership style (β = 0.232), and charismatic leadership style (β = 0.153) have a positive and significant effect on employee performance. Furthermore, these three leadership styles had a positive and significant effect on knowledge sharing, and knowledge sharing also influenced employee performance (β = 0.288). The mediating role of knowledge sharing in the relationship between leadership styles and performance was confirmed. Customs managers can improve employee performance by strengthening strategic leadership styles and fostering a culture of knowledge sharing.